2020
DOI: 10.1111/cpr.12955
|View full text |Cite
|
Sign up to set email alerts
|

The calcium channel TRPV6 is a novel regulator of RANKL‐induced osteoclastic differentiation and bone absorption activity through the IGF–PI3K–AKT pathway

Abstract: Objectives Calcium ion signals are important for osteoclast differentiation. Transient receptor potential vanilloid 6 (TRPV6) is a regulator of bone homeostasis. However, it was unclear whether TRPV6 was involved in osteoclast formation. Therefore, the aim of this study was to evaluate the role of TPRV6 in bone metabolism and to clarify its regulatory role in osteoclasts at the cellular level. Materials and methods Bone structure and histological changes in Trpv6 knockout mice were examined using micro‐compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Extensive studies have indicated that RANKL induces oscillatory changes in intracellular Ca 2+ concentrations and activates nuclear factor of activated T cells c1 (NFATc1), resulting in osteoclast-specific gene transcription to induce osteoclast differentiation. 34 GO created evidencesupported annotations to help predict the biological roles of genes regulated by Epimedin B by classifying them using ontologies in a computable collaborative way and the results suggested that the genes affected by Epimedin B involved in biological roles related to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have indicated that RANKL induces oscillatory changes in intracellular Ca 2+ concentrations and activates nuclear factor of activated T cells c1 (NFATc1), resulting in osteoclast-specific gene transcription to induce osteoclast differentiation. 34 GO created evidencesupported annotations to help predict the biological roles of genes regulated by Epimedin B by classifying them using ontologies in a computable collaborative way and the results suggested that the genes affected by Epimedin B involved in biological roles related to osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies have shown that growth factors such as insulin and insulin-like growth factor (IGF) can activate the PI3K/Akt signaling pathway, thereby affecting the formation, differentiation and function of osteoblasts and osteoclasts, and play a role in regulating bone mass and bone strength. 34 Akt, also known as protein kinase B (PKB), is a serine/threonine specific protein kinase. Akt1 can phosphorylate FoxO3a and prevent it from accumulating to the nucleus, which can transactivate the destruction of the pro-apoptotic molecule (Bim) in osteoblasts of its downstream target gene, thereby inhibiting osteogenic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The TRP cation channels also make a contribution to osteoclast differentiation, for example, TRPC1, TRPV4, and TRPV5 are essential for the regulation of osteoclastogenesis [ 56 58 ]. In a recent study, osteoporosis and enhanced bone absorption were found in TRPV6 knockout mice [ 59 ]. TRPV6 channels decreased the ratios of phosphorylation in the PI3K-AKT pathway which mediates the regulation of osteoclast formation and bone resorption ( Figure 2e ) [ 59 ].…”
Section: Ca 2+ Channelsmentioning
confidence: 99%